Performance of sweet gourd as relay with transplanted aman rice under rainfed ecosystem in Sylhet region - Nazrul, MI; Shaheb, MR (Bangladesh Agronomy Journal, 2015)
This study was carried out to evaluate the economic benefits of sweet gourd relay with transplanted aman rice under farmers field condition at Farming System Research and Development (FSRD) site, Jalalpur and Multi Location Testing (MLT) site, Zakigonj of Sylhet region during 2012-2013 and 2013-2014. The treatment combinations T1: T. aman rice / sweet gourd (var. Mollika), T2: T. aman rice / sweet gourd (var. Hatirpara) local, T3: Sweet gourd (var. Mollika) sole, T4: Sweet gourd (var. Hatirpara) sole and T5: T. aman rice sole (var. Binadhan-7) was maintained. The study was based in a randomized complete block (RCB) design with six dispersed replications. Results in terms of the crops yield, rice equivalent yield, gross return and net return with benefit cost ratio showed higher in sweet gourd / transplanted aman rice relay cropping system. So, sweet gourd relayed with transplanted aman rice could be an economically viable technology, instead of sole cropping, for best utilization of fallow land with residual soil moisture in Sylhet region. Bangladesh Agron. J. 2014, 17(2): 47-53